Patients With Epilepsy Who Underwent Epilepsy Surgery During the COVID-19 Pandemic Showed Less Depressive Tendencies - Niimi, Keiko; Fujimoto, Ayataka; Sato, Keishiro; Enoki, Hideo; Okanishi, Tohru (Frontiers in Neurology, 2021)
Introduction: Our hypothesis in this study was that differences might exist between patients with epilepsy (PWE) who underwent epilepsy surgery before and within the period of the coronavirus disease 2019 (COVID-19) pandemic. The purpose of this study was to compare results of the Zung Self-Rating Depression Scale (SDS) between PWE who underwent epilepsy surgery before and during the pandemic period. Methods: Participants were PWE who underwent open cranial epilepsy surgery between February 2019 and February 2021 in our hospital. Patients who underwent surgery in the first half of this period, between February 2019 and January 2020, were defined as the pre-pandemic period group (pre-Group) and those treated in the second half, between February 2020 and February 2021, were categorized as the pandemic period group (within-Group). All patients completed the SDS before surgery, and scores were compared between groups. Results: SDS score was significantly higher in the pre-Group than in the within-Group (p = 0.037). Other factors, including age (p = 0.51), sex (p = 0.558), epilepsy duration from onset to SDS score evaluation (p = 0.190), seizure frequency (p = 0.794), number of anti-seizure medications (p = 0.787), and intelligence quotient (p = 0.871) did not differ significantly between groups. Conclusion: SDS score was higher in the pre-pandemic group than in the within-pandemic group, which may indicate that PWE with less-positive outlooks may be less likely to seek medical attention during stressful periods.